Phytochemicals and Carbohydrates Content of Some Indigenous Leafy Vegetables of Jorhat District, India - Choudhury, B.H.; Baruah, A.M.; Baishya, S. (Asian Journal of Chemistry, 2018)
Some indigenous leafy vegetables were collected from various places of Jorhat district, Assam state of India for evaluation of phytochemicals and carbohydrates contents. The total alkaloid contents varied from 0.13-3.23 %, total phenol content varied from 0.25-2.2 %, total flavanoids content varied from 0.86-3.40%, total flavanol content varied from 0.33-1.63 %. In case of carbohydrates, starch content varied from 18.78-56.42 %, total soluble sugar content varied from 7.37-21.69 and reducing sugar content varied from 4.19-18.58 %.